2005
DOI: 10.4049/jimmunol.174.1.180
|View full text |Cite
|
Sign up to set email alerts
|

CD28 Regulates the Translation of Bcl-xL via the Phosphatidylinositol 3-Kinase/Mammalian Target of Rapamycin Pathway

Abstract: In concert with the TCR, CD28 promotes T cell survival by regulating the expression of the antiapoptotic protein Bcl-xL. The mechanism by which CD28 mediates the induction of Bcl-xL remains unknown. We show that although signaling through the TCR is sufficient to stimulate transcription of Bcl-xL mRNA, CD28, by activating PI3K and mammalian target of rapamycin, provides a critical signal that regulates the translation of Bcl-xL transcripts. We observe that CD28 induced 4E-binding protein-1 phosphorylation, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 63 publications
(56 reference statements)
7
43
0
Order By: Relevance
“…More recent evidence, however, proposed mTOR as a target of CD28-dependent signaling (24,51). Accordingly, we found that the engagement of TCR and CD28 induces the rapid and RAPA-sensitive phosphorylation of p70…”
Section: Discussionmentioning
confidence: 64%
“…More recent evidence, however, proposed mTOR as a target of CD28-dependent signaling (24,51). Accordingly, we found that the engagement of TCR and CD28 induces the rapid and RAPA-sensitive phosphorylation of p70…”
Section: Discussionmentioning
confidence: 64%
“…In particular, one tyrosine (Y170 in mouse CD28, Y173 in human CD28) that is important in PI3K activation permits CD28 to recruit SH2-containing signaling molecules, including PI3K, Grb2, and Gads that control the regulation of bcl-xL (21,74). However, whether or not this regulation was dependent on mammalian target of rapamycin pathway is still controversial (13,75). CD28 also promotes expression of bcl-2, bfl-1 (A1), and myeloid cell leukemia sequence 1 (mcl-1) to regulate T cell survival (76)(77)(78).…”
Section: Cell Survivalmentioning
confidence: 99%
“…CD28 costimulation leads to a dramatic upregulation of IL-2 expression through enhanced transcription and mRNA stabilization (12). In addition, CD28 costimulation also plays an important role in T cell survival, by inducing the expression of antiapoptotic protein bcl-xL and regulating the metabolic activity of T cells (13). Finally, CD28 plays a crucial role on the generation of Th2 responses (14).…”
Section: Introductionmentioning
confidence: 99%
“…As such, we hypothesized that an enhanced efficacy of rapamycin-generated T cell therapy may be associated with an increase in T cell survival posttransplant. An ability of rapamycin to confer a T cell survival advantage seems somewhat paradoxical because receptor signaling for the prosurvival cytokines IL-7 (20) and the prosurvival costimulatory signal CD28 (21,22) used in our ex vivo T cell expansion method are dependent in part upon mammalian target of rapamycin (mTOR) function. In contrast, mTOR inhibition can mediate antiapoptotic effects in several experimental models (reviewed in Ref.…”
mentioning
confidence: 99%